Effects of an Educational Intervention Program on Positional Cranial Deformity in Premature Infants - Alexandra Mosca-Hayler; Daniela López-Schmidt; Romina Curotto-Noce; Jorge Cuevas-Aburto; Jaime Vásquez-Gómez; Samuel Durán-Agüero; Juana Borja González; Ximena Diaz-Martínez; Rafael Zapata-Lamana; María Antonia Parra-Rizo; Igor Cigarroa (MDPI AG, 2024)
Positional cranial deformities are associated with prematurity evolving during the first 2 years of life due to the malleable characteristics of the skull, the first year being the main/primary therapeutic window for intervention. The objectives were (a) to describe health characteristics, peri- and postnatal pathologies, and positional cranial deformities in infants enrolled in an early intervention program and (b) to analyze the effects of a parent education-based intervention program on positional cranial deformity in premature infants. A quantitative, analytical, longitudinal study was conducted. It included 103 premature infants enrolled in an early intervention program (EIP) during the year 2017, all under 4 months of corrected age, to whom a parent education-based intervention program was applied. Cranial circumference, cranial width, diagonals, and anteroposterior diameter were measured, and the cranial asymmetry index (CAI) and cephalic index (CI) were calculated at baseline and during two subsequent evaluations separated by a 3-month period. The main results showed that 75.7% of the infants belonged to a very premature gestational age category, and 57.3% had an adequate weight for gestational age. The most frequent pathologies were premature jaundice, premature anemia, and hyaline membrane disease. The most frequent positional cranial deformity was plagiocephaly. The parent education-based intervention program resulted in (1) a significant decrease in the CAI and a significant increase in the IC, (2) plagiocephalies: an increase in the mild category and a decrease in the moderate + severe categories, (3) brachycephalies: a decrease in the absence category and an increase in the moderate + severe category, and (4) dolichocephalies: an increase in the absence category and a decrease in the mild category. In conclusion, the recommended first line of intervention was not enough for this population, and future studies should support the development of national clinical guidelines, where education is complemented with other therapeutic measures.